Perceptions of pre-retired employees of a public university about retirement - Desirée Ariane Modos Figueira; Maria do Carmo Lourenço Haddad; Raquel Gvozd (Rev Rene)
Objective: to unveil the perceptions of pre-retired employees of a public university about retirement. Methods: qualitative research conducted with 16 pre-retired employees of a public university. Data were collected in monthly meetings in three focus groups that discussed aspects related to retirement and were analyzed by content analysis technique.Results: when identifying retirement as a possibility, pre-retired workers rescued the meaning of work, reflected on the life changes that retirement can lead and signaled the need for strategies for experiencing retirement. Conclusion: retirement brings up positive and negative perceptions, concerns and questions that reinforce the need to offer to pre-retired workers the opportunity to reflect on this stage of life and prepare to enjoy the post-career period with quality.